2013
DOI: 10.1074/jbc.m113.476887
|View full text |Cite
|
Sign up to set email alerts
|

Reinterpreting the Action of ATP Analogs on KATP Channels

Abstract: Background: Stimulation by post-hydrolytic, ADP-bound conformations of SUR1 underlies current models of K ATP channel activation; ATP analogs are assumed to lower activity by reducing hydrolysis. Results: ATP␥S switches conformations with lowered affinity; AMP-PxP selectively bind NBD1, preventing switching. Conclusion:The actions of ATP analogs on K ATP channels require reinterpretation. Significance: Reduced affinities of SUR1 NBDs for ATP analogs limit conformational switching and channel activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
37
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 58 publications
(58 reference statements)
7
37
0
Order By: Relevance
“…Fap7•AMPPCP provides intermediate level of protection. Similar compromised activity from the non-hydrolyzable ATP analog has been observed in other systems (Ortiz et al, 2013; Yount et al, 1971). Together, these data strongly suggest that 80S-like ribosomes are in the classic conformation, and that addition of Fap7•ATP promotes formation of the rotated state.…”
Section: Resultssupporting
confidence: 81%
“…Fap7•AMPPCP provides intermediate level of protection. Similar compromised activity from the non-hydrolyzable ATP analog has been observed in other systems (Ortiz et al, 2013; Yount et al, 1971). Together, these data strongly suggest that 80S-like ribosomes are in the classic conformation, and that addition of Fap7•ATP promotes formation of the rotated state.…”
Section: Resultssupporting
confidence: 81%
“…Studies on CFTR and SUR1 revealed that AMP-PNP is a poor ATP analog in heterodimeric ABC exporters. For CFTR, a 20-fold decreased opening rate was observed for AMP-PNP compared with ATP (31) and in SUR1, AMP-PNP fails to support NBD dimerization and conformational switching (32).…”
Section: Discussionmentioning
confidence: 99%
“…Chemical shift mapping also indicates that transient interactions occur with NBD1 residues that bind NBD2. Phosphorylation promotes stabilization of NBD1 into a conformation that allows NBD1 to make productive interactions (80), such as with MgATP and/or NBD2, leading to increased K ATP channel opening (12). Thus, the model (Fig.…”
Section: Discussionmentioning
confidence: 99%